Resisting in Silence: Coping with Gender-Based Violence among Internally Displaced Persons in Cameroon - Che, Julien Ngum; Vubo, Emmanuel Yenshu; Abonge, Christiana Vegah (Advances in Social Sciences Research Journal, 2026)
The phenomenon of Gender-Based Violence (GBV) remains a significant problem in zones of conflict, particularly among Internally Displaced Persons (IDPs). Survivors of GBV in Cameroon experience continuous sexual, physical, emotional, and economic violence perpetrated by husbands, armed men, community members, and at times, by humanitarian workers. This study aims to understand the coping strategies of these survivors, which, in most GBV studies, are rarely the focus of attention. The study aims to answer the following three questions: which coping strategies are adopted by Internally Displaced Survivors of GBV in Tiko Sub-Division, Cameroon? How do gender, religion, social support networks, and other relevant factors influence these choices? How do the survivors themselves assess the impact of the coping strategies adopted? A mixed-methods approach that integrates quantitative and qualitative data was employed in this study. One hundred IDP survivors of GBV participated in the study, comprising 76 women and 24 men, through quantitative surveys and qualitative in-depth interviews. The study was guided and analyzed through the Feminist Theory, the Social Ecological Model, and the Power and Control Wheel, which explains the causes of GBV and the power relations involved. These insights assist us in understanding the impact of harmful customs, pervasive gender discrimination, inadequate protective measures, and prevailing conflicts on the risks and experiences of GBV. The results emphasize the lack of more comprehensive support systems centered on the survivor.